Investigation of antiproliferative effects of gamma- and delta-tocotrienols in human breast cancer cell lines using genomics and quantitative proteomics approach / Premdass Ramdas - Premdass, Ramdas (2019)
The chemoprevention of breast cancer using natural and synthetic compounds to intervene in the early precancerous stages of carcinogenesis before the invasion begins is undertaken as a measure to reduce breast cancer probability for women at high risk. A number of bioactive dietary components are of particular interest in the field of breast cancer. One such compound known as the tocotrienols; a sub-group of Vitamin E family, display anticancer properties and may play a role in cancer prevention. To date, there are many studies which show that tocotrienols can inhibit the proliferation of human breast cancer cells in vitro. Especially, the ?- and ?- isoforms of tocotrienols have been shown to have a more potent inhibitory effect on numerous cancer cell growth. In this study, the effect of tocotrienol isomers (? and ?) were used to postulate the mechanism of action of these compounds on DNA methylation process and proteomic footprinting. The use of DNA methylation profiling and quantitative proteomics provided insights into functions and the mechanisms of tocotrienols action in breast cancer. The DNA methylation profiling of known tumour suppressors of breast cancer revealed significant DNA hypomethylation in ?- and ?-tocotrienols-treated MCF-7 and MDA-MB-231 cells. Tocotrienols treatment resulted in methylation changes at the methylated CpG sites of some important tumour suppressor genes such as Hs3st2, Adam23, Cav1 and Cst6. These genes were hypermethylated in untreated cells, but the percentage of methylation was reduced significantly following ?- and ?-tocotrienols treatment which showed the ability of these isomers to potentially reverse the DNA methylation alterations. The data provided new evidence for tocotrienols-mediated DNA methylation alterations as a potential mechanism of breast cancer chemoprevention. The supernatant, cytoplasmic and nuclear protein proteomic profiles of tocotrienols treated MCF-7 and MDA-MB-231 human breast cancer cells were analysed by utilising label-free quantitative proteomic strategy. The key findings of secreted proteomic analysis following tocotrienols iv treatment showed downregulation of Cathepsin D expression which is frequently seen over-expressed in various cancer and upregulation of Profilin-1 whose downregulation was reported in various adenocarcinoma. Next, the quantitative label-free proteome profiling of nuclear and cytoplasmic protein of ?- and ?-tocotrienol treated MCF-7 and MDA-MB-231 cells showed the ability of tocotrienols to dysregulate the proteins involved in cell motility, trafficking, metastasis, invasion and proliferation. The cytoplasmic proteome results revealed the ability of tocotrienols to inhibit a group of proteasome proteins such as Psma, Psmb, Psmd and Psme. As the inhibition of proteasome proteins are known to induce apoptosis in proliferating or transformed cells, the findings from this study identified tocotrienols as a potential proteasome inhibitor that can overcome deficiencies in growth-inhibitory or pro-apoptotic molecules in breast cancer cells. Keywords: Vitamin E, Tocotrienols, Proteomics, Genomics, Breast Cancer.